SEASONAL AND GEOGRAPHIC VARIATIONS OF METHANESULFONIC-ACID IN THE ARCTIC TROPOSPHERE - Li, S. M.; Barrie, L. A.; TALBOT, RW; HARRISS, RC; DAVIDSON, CI; JAFFREZO, JL (ATMOSPHERIC ENVIRONMENT PART A-GENERAL TOPICS, 1993)
Measurements in the Arctic troposphere over several years show that MSA concentrations in the atmospheric boundary layer, 0.08-6.1 parts per trillion (ppt, molar mixing ratio), are lower than those over mid-latitude oceans. The seasonal cycle of MSA at Alert, Canada (82.5 degrees N, 62.3 degrees W), has two peaks of 6 ppt in March-April and July-August and minima of 0.3 ppt for the rest of the year. At Dye 3 (65 degrees N, 44 degrees W) on the Greenland Ice Sheet, a similar seasonal MSA cycle is observed although the concentrations are much lower with a maximum of 1 ppt. Around Barrow, Alaska (71.3 degrees N, 156.8 degrees W), MSA is between 1.0 and 25 ppt in July, higher than 1.5+/-1.0 ppt in March-April. The mid-tropospheric MSA level of 0.6-1 ppt in the summer Arctic is much lower than about 6 ppt in the boundary layer. Al Alert, the ratio of MSA to non-sea-salt (nss) SO42- ranges from 0.02 to 1.13 and is about 10 times higher in summer than in spring. The summer ratios are higher than found over mid-latitude regions and, when combined with reported sulfur isotope compositions from the Arctic, suggest that on average a significant fraction (about 16-23%) of Arctic summer boundary layer sulfur is marine biogenic. The measurements show that the summer Arctic boundary layer has a significantly higher MSA/nss-SO42- ratio than aloft.